2019
DOI: 10.14710/jitpi.2019.6745
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH PENAMBAHAN TEPUNG KARAGENAN PADA KARAKTERISTIK BAKSO KERANG DARAH (Anadara granosa)

Abstract: Kerang darah merupakan salah satu hasil perikanan yang banyak diminati oleh masyarakat. Pemanfaatan kerang darah dengan menggunakannya sebagai bahan pembuatan bakso merupakan salah satu solusi dan meningkatkan value dari produk ini sendiri. Karagenan adalah polimer polisakarida bersifat hidrofilik yang dapat di ekstrak dari rumput laut merah (Rhodophyceae) dengan jenis Euchema cottonii. Rumput laut dengan jenis E. cottonii banyak ditemukan di Indonesia. Penelitian Penambahan karagenan sebagai bahan pembuat gel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
(1 reference statement)
0
6
0
1
Order By: Relevance
“…EPA is 2.39%, 3.27% (Patty et al, 2023). Bakso is a processed meat product that is mixed with starch and spices, with or without the addition of other food ingredients, which is shaped round or in other forms and cooked through boiling or steaming processes (Nurwin et al, 2019). The processing of blood cockle meatballs begins with mixing the blood cockles and tuna that has been ground, then combining it with other weighed additional ingredients as shown in Figure 3.…”
Section: Schedule and Stages Of Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…EPA is 2.39%, 3.27% (Patty et al, 2023). Bakso is a processed meat product that is mixed with starch and spices, with or without the addition of other food ingredients, which is shaped round or in other forms and cooked through boiling or steaming processes (Nurwin et al, 2019). The processing of blood cockle meatballs begins with mixing the blood cockles and tuna that has been ground, then combining it with other weighed additional ingredients as shown in Figure 3.…”
Section: Schedule and Stages Of Implementationmentioning
confidence: 99%
“…Blood cockles are a popular seafood among communities. Utilizing blood cockles as raw material for making meatballs provides a solution and enhances the value of the product itself (Nurwin et al, 2019). Blood cockles are also rich in iron, which is highly beneficial for health.…”
Section: Introductionmentioning
confidence: 99%
“…Huruf superscripts yang berbeda pada perlakuan menunjukkan berbeda nyata pada p<0,05 Kenampakan kolagen kulit ikan payus memiliki warna cerah dan agak kekuningan, berbentuk seperti kristal dan sangat tipis, serta mudah menempel jika dibiarkan pada kondisi terbuka. Nurwin et al (2019) menjelaskan bahwa faktor pertama yang dipertimbangkan panelis saat memilih suatu produk adalah kenampakannya, meskipun kenampakan tidak secara langsung memengaruhi tingkat sensorik, hal itu berdampak pada penerimaan konsumen. Temuan analisis Kruskal-Wallis mengungkapkan bahwa faktor konsentrasi NaOH tidak berpengaruh terhadap kenampakan kolagen.…”
Section: Kadar Airunclassified
“…The results of this study showed that the ash content obtained from the meat was 0.87 %. According to [19] the ash content is consist of various types of minerals with varying compositions depending on the type and source of food. Ash content is a non-volatile component and remains in the combustion and ignition of organic compounds [20].…”
Section: Ash Contentmentioning
confidence: 99%
“…The results of this study showed that the fat content in meat was 7.25 %. Fat in fish meat consists of 95% of triglycerides and their constituent fatty acids are straight chains [19].…”
Section: Fat Contentmentioning
confidence: 99%